The Methodology of Muhadithīn in dealing with the Phenomenon of Difference of Narrations - Saleha Batool (jihat-ul-islam, 2021)
One of the most significant branches of Knowledge in Islamic Sciences is the science of hadiīh. For it is the expertise of Muslim scholars to develop the tools for establishing the chain of Narrators (isnād) by critically evaluating the text and the chain of narrators. As the narrators being human have different capacities so it is quite obvious that all of them do not have the same level of memory and ability to transmit, which can result in the difference of words while narrating and sometimes to contradictory expressions in narrations. This research is an attempt to study this phenomenon in different perspectives and to explore that how this phenomenon has been regulated by muhadithīn and how they critically judge the difference of narrations. What are the measures and procedures adopted by them to evaluate these narrations and how they prefer one of the narrations on the other following the narrators through time and space, observing their memory status and evaluating their learning abilities and judging their transmitting methods.